Invasive coronary imaging of inflammation to further characterize high-risk lesions: what options do we have? - Los, Jonathan; Mensink, Frans B.; Mohammadnia, Niekbachsh; Opstal, Tjerk S. J.; Damman, Peter; Volleberg, Rick H. J. A.; Peeters, Denise A. M.; van Royen, Niels; Garcia-Garcia, Hector M.; Cornel, Jan H.; El Messaoudi, Saloua; van Geuns, Robert-Jan M. (Frontiers in Cardiovascular Medicine, 2024)
Coronary atherosclerosis remains a leading cause of morbidity and mortality worldwide. The underlying pathophysiology includes a complex interplay of endothelial dysfunction, lipid accumulation and inflammatory pathways. Multiple structural and inflammatory features of the atherosclerotic lesions have become targets to identify high-risk lesions. Various intracoronary imaging devices have been developed to assess the morphological, biocompositional and molecular profile of the intracoronary atheromata. These techniques guide interventional and therapeutical management and allow the identification and stratification of atherosclerotic lesions. We sought to provide an overview of the inflammatory pathobiology of atherosclerosis, distinct high-risk plaque features and the ability to visualize this process with contemporary intracoronary imaging techniques.